(untitled) (Comprehensive Journal of Science, 2025)
: Sustainability refers to the capacity of systems and processes to operate, evolve, and generate outcomes over the long term without harming the environment while safeguarding future generations’ rights. Developing countries face significant challenges due to rapid technological advancements and the knowledge explosion, requiring strategic and scientifically informed approaches to adapt effectively. Technical and vocational education (TVE) plays a vital role in this context by preparing skilled human resources capable of responding to scientific, technological, and professional developments and meeting the evolving demands of the labor market. Advanced nations rely on modern educational institutions, often referred to as “knowledge factories,” which aim to produce highly competent personnel, foster innovation, and strengthen competitiveness both nationally and internationally. In Libya, however, TVE faces multiple challenges, including insufficient infrastructure, a shortage of qualified teaching and technical staff, limited practical training, and inadequate alignment between educational programs and labor market requirements. This study examines the current state of technical and vocational education in Libya, identifying key barriers to its sustainability, such as gaps in strategic planning, limited financial and technical support, and challenges in aligning graduates’ skills with market demands. It also explores the roles of society, academic staff, and administrative bodies in enhancing the effectiveness of TVE. Recommendations are proposed to improve curricula, strengthen infrastructure, and develop graduates’ competencies to meet future labor market needs. The findings underscore that sustainable TVE is essential for cultivating a productive, innovative, and adaptable workforce capable of addressing contemporary challenges and contributing to long-term socio-economic development. Investment in well-qualified human resources and the implementation of innovative educational programs are fundamental to achieving this goal